2018
DOI: 10.1002/bip.23225
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the structure of a novel artificial heme‐enzyme with peroxidase‐like activity: A theoretical investigation

Abstract: Fe(III)-Mimochrome VI (MC6) is a recently reported artificial heme-peptide conjugate system with a high peroxidase-like activity. By design, its structure features a five-coordinated Fe(III)-deuteroporphyrin active site, embedded in a compact α-helix-heme-α-helix "sandwich" motif. Up to now, no detailed MC6 structural characterization is available. In this work we propose a theoretical investigation based on molecular dynamics (MD) simulations and hybrid quantum mechanics/molecular mechanics (QM/MM) optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Indeed, the spectroscopic characterization of the isolated Fe MC6* C-I derivative confirmed this hypothesis [263]. As a further support, theoretical analysis identified the Arg10(D)-Glu2(TD) as the weaker among the four ion pairs occurring in MC6 analogues [255].…”
Section: Fig 8 Fe(iii)-mimochrome Peroxidase Activity Freely Diffusmentioning
confidence: 62%
See 1 more Smart Citation
“…Indeed, the spectroscopic characterization of the isolated Fe MC6* C-I derivative confirmed this hypothesis [263]. As a further support, theoretical analysis identified the Arg10(D)-Glu2(TD) as the weaker among the four ion pairs occurring in MC6 analogues [255].…”
Section: Fig 8 Fe(iii)-mimochrome Peroxidase Activity Freely Diffusmentioning
confidence: 62%
“…UV-Vis analysis suggested that ferric MC6 could be in the high-spin (S = 5/2) state; however, resonance Raman spectroscopy suggested that it could be best described as an admixed state (S = 3/2, 5/2) [249], as already observed in Cyt c and in artificial peroxidases [253,254]. The generation of this electronic state was recently supported by a QM-MM (quantum mechanics/molecular mechanics) analysis [255]. Electrochemical analysis was performed on FeMC6 either when adsorbed on electrode surface or freely diffusing in solution ( Table 1).…”
Section: Designed Models Of Penta-coordinated Mimochomes (A) Mc6; (Bmentioning
confidence: 70%
“…The implicit and structureless solvent surrounding the explicit sphere was accounted for in the energy potential and completed the hybrid explicit/implicit solvation model. More specifically, nonperiodic boundary conditions accounted for the interactions of both electrostatic and dispersion–repulsion nature between the explicit molecular system and the implicit bulk solvent. The solvent molecules were explicitly represented by the TIP3P water model, while the implicit bulk solvent was represented by the polarizable continuum model in its conductor-like version. , The explicit system itself is treated at different levels of theory according to the hybrid QM/MM ONIOM extrapolative method employing an electronic embedding scheme. In particular, the pyranine–water–acetate system is described by DFT and TD-DFT in the ground and excited electronic state, respectively, by adopting the global hybrid B3LYP functional and the 6-31g­(d,p) basis set. The obtained energy potential ruled the AIMD simulations in both the ground and the first singlet excited state.…”
Section: Methodsmentioning
confidence: 99%
“…The 6-31+G­(d,p) basis set was adopted for C, H, and O, whereas the Fe atom was described by the LANL2DZ basis set and the associate effective core potential, which was demonstrated to be a suitable choice to describe the reactivity of metal centers. …”
Section: Methodsmentioning
confidence: 99%